The Great Crash 1929: the clasic study of that disaster - Galbraith John Kenneth (London; Boston, Houghton Mifflin: Penguin Books, 1955)
This classic tome is a detailed economic examination of the 1929 financial collapse written with wit and attitude.
Includes index (212-222)
nmn 25/07/13
Loans
Keywords: .Depressions -- 1929 -- United States. Stock Market Crash -- 1929.